Single-molecule magnet behavior in a mononuclear dysprosium(iii) complex with 1-methylimidazole. Issue 5 (12th January 2017) - Yao, Binling; Gu, Bin; Su, Meihui; Li, Guoliang; Ma, Yue; Li, Licun; Wang, Qinglun; Cheng, Peng; Zhang, Xuan
Abstract : Using 1-methylimidazole ligand and Dy(hfac)3 ·2H2 O salt achieved a new single-molecule magnet of [Dy(hfac)3 ·(1-MeIm)2 ] with an energy barrier of 42.54 K. Abstract : Three novel mononuclear lanthanide complexes coordinated with 1-methylimidazole [Ln(hfac)3 ·(1-MeIm)2 ] (Ln = Dy(1 ), Tb(2 ) and Ho(3 ), hfac = hexafluoroacetylacetonate, 1-MeIm = 1-methylimidazole) have been designed and characterized by single-crystal X-ray diffraction, luminescence and magnetic measurements. Studies indicate that the metal ions of all three mononuclear complexes adopt a slightly distorted D 4d [LnO6 N2 ] coordination environment, which is formed by two terminal 1-methylimidazole ligands and three bischelating hfac − anions. Frequency dependent out-of-phase signals were observed for complex1 in dynamic magnetic susceptibility measurements, which indicates single-molecule magnetic behavior.